Comparative Cardioprotective Effect of Herbs of Hridya dashemani (Karamarda- Carissa carandas L., Badara- Ziziphus jujuba Lam.) versus Arjuna-Terminalia arjuna (Roxb.ex.DC.) Wight & Arn. against Isoprenaline induced Myocardial Infarction in Rats (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Hridya dashemani, (ten cardioprotective herbs) includes fruits of Amra, Amrataka, Lakucha, Karamarda, Vrukshamla, Amlavetasa, Kuvala, Badara, Dadima and Matulunga. In Ayurveda, these herbs have been known to be conducive to heart. The present study was designed to evaluate the cardioprotective action of two herbs of Hridya dashemani [fruits of Karamarda (Carissa carandas L.) and fruits of Badara (Ziziphus jujuba Lam.)] on the basis of biochemical & histopathological parameters in isoprenaline (ISO) induced myocardial infarction (MI) in experimental rats and to compare with stem bark of Arjuna (Terminalia arjuna (Roxb.ex.DC.) Wight & Arn.), a well-known cardioprotective herb. Thirty-six male wistar albino rats were randomly divided into six groups. Group I- Normal control (NC), Group II- ISO induced MI, Group III- Positive control with Hesperidin (100mg/kg b.w), Group IV- Badara (Z. jujuba - 450mg/kg b.w), Group V-Karamarda (C. carandus - 450mg/kg b.w), Group VI-Arjuna (T.arjuna - 450mg/kg b.w). After 21 days of pre-treatment, experimental MI was induced in all groups except NC by injecting ISO subcutaneously (85 mg/kg) on 19th & 20th day at an interval of 24 hr. Serum biochemical parameters including cardiac biomarkers and histopathological examination of heart tissues were evaluated. ISO treated rats had a significant (P < 0.05) elevation in serum levels of diagnostic marker enzymes (AST, ALT, CK-MB, LDH, ALP) when compared to NC. All the pre-treated groups had significantly (P < 0.05) reduced serum levels of marker enzymes when compared to ISO treated control. The protective role of these herbs was further confirmed by histopathological examination. Comparison revealed that Karamarda (C. carandus) pre-treated had similar protective effect as Arjuna (T. arjuna) in various biochemical parameters (AST, ALT, ALP, LDH, CK-MB, HDL, Cholesterol, Creatinine). It may be concluded from the present study that 450mg/kg b.w of water extract of the above herbs have cardioprotective action against isoprenaline induced MI, with Karamarda (C. carandus) & Arjuna (T. arjuna) having almost similar effects. The study paves way to further evaluate these herbs as preventive and curative in the clinical management of cardiovascular disease (CVD).